Design and Implementation of a Cognitive Simulation Model for Robotic Assembly Cells - Faber, Marco; Kuz, Sinem; Mayer, Marcel Ph; Schlick, Christopher M. (Engineering Psychology and Cognitive Ergonomics. Understanding Human Cognition, 2013)
Against the background of a changing global economy, new production technologies have to be developed to stay competitive in high-wage countries. Therefore, an integrated cognitive simulation model (CSM) has been developed to support the human operator and the assembly process. By making the behavior of the system more intuitive the cognitive compatibility between the operator and the production system is enhanced significantly. The presented CSM faces three different challenges: (1) visualizing the behavior of the system to give the human operator an understanding of the technical systems, (2) cognitive control of a real robotic assembly cell and (3) performing mass simulations in order to evaluate parameters, new assembly or planning strategies or the assembly of new products. Additionally, a graph-based planner supports the cognitive planning instance for realizing complex tasks.